The Spongebob movie. Sponge out of water [videorecording (DVD)] - Kenny, Tom, 1962-; Banderas, Antonio; Conway, Tim (Paramount Pictures, 2015)
When pirate Burger Beard steals the secret recipe for the beloved Krabby Patties, SpongeBob and friends come ashore to bring back the missing formula. To succeed, they must team up with former rival, Plankton, but soon realize that to defeat a super-villain, they must unleash their inner superheroes.